2017
DOI: 10.1007/s11302-016-9554-z
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of sinomenine in diabetic neuropathic pain mediated by the P2X3 receptor in dorsal root ganglia

Abstract: Type 2 diabetes mellitus (T2DM) accounts for more than 90% of all cases of diabetes mellitus (DM). Diabetic neuropathic pain (DNP) is a common complication of T2DM. Sinomenine is a natural bioactive component extracted from the Sinomenium acutum and has anti-inflammatory effects. The aim of our study was to investigate the effects of sinomenine on DNP mediated by the P2X receptor in dorsal root ganglia (DRG). The mechanical withdrawal threshold (MWT) and thermal withdrawal latency (TWL) in T2DM rats were lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…P2X3R antagonists have been proposed for the treatment of diabetic neuropathic pain ( Guo et al, 2015 ; Zhang et al, 2015b ; Peng et al, 2017 ; Rao et al, 2017 ). Recently P2X7R have also been claimed to be involved in painful diabetic neuropathy in rats ( Liu et al, 2017 ).…”
Section: Endocrine Diseasesmentioning
confidence: 99%
“…P2X3R antagonists have been proposed for the treatment of diabetic neuropathic pain ( Guo et al, 2015 ; Zhang et al, 2015b ; Peng et al, 2017 ; Rao et al, 2017 ). Recently P2X7R have also been claimed to be involved in painful diabetic neuropathy in rats ( Liu et al, 2017 ).…”
Section: Endocrine Diseasesmentioning
confidence: 99%
“…Sinomenine, an alkaloid derived from Sinomenium acutum , is a chief ingredient that has been reported to have a variety of pharmacological properties including anxiolytic effects ( Rao et al ., 2017 ). From a recent experiment, sinomenine enhanced pentobarbital-induced sleeping behaviors, and modulate sleep architecture via GABA A -ergic systems in rodents, ultimately increasing NREM sleep.…”
Section: Natural Products Which Have Proven To Be Effective For Sleepmentioning
confidence: 99%
“…Many alkaloids such as SIN, disinoimenine, sinactine, sinoactine, acutumine, and magnoflorine, as well as the lignan syringaresinol have been isolated from Sinomenium acutum ( Bao et al ., 2005 ; Wang et al ., 2007 ; Jin et al ., 2008 ). Among them, SIN has been reported to have a variety of pharmacological effects including anti-rheumatism, immunomodulation and sedative effects ( Chen et al ., 1997 ; Li et al ., 2003 ; Rao et al ., 2017 ). Recently, it was reported that Sinomenium acutum , has sedative and anxiolytic effects mediated by GABA-ergic systems.…”
Section: Discussionmentioning
confidence: 99%
“…Sinomenine (SIN; Fig. 1 ), an alkaloid derived from Sinomenium acutum , is a chief ingredient which has been reported to have a variety of pharmacological effects including anti-rheumatism, immunomodulation and anxiolytic-like effects ( Chen et al ., 1997 ; Li et al ., 2003 ; Rao et al ., 2017 ). However, it has not been studied whether SIN is sedative or affects sleep behaviors.…”
Section: Introductionmentioning
confidence: 99%